The influence of learning space colours on students within attention, emotional and behavioural - Duyan, Fazila; Unver, Fatma Rengin (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2022)
Environmental colours can affect users in terms of performance, aesthetics, emotion, etc., and can play a role in their actions. Previous studies have shown that environmental colours are effective on user perception. This research aims to find out how wall colours can impact students in the learning environment by manipulating their attention, emotion, and behavioural reactions. An experiment was conducted with students aged 8-9 years in a real classroom painted in twelve colours. The students have taken the courses within a classroom having different wall colours (red, yellow, green, blue, purple, orange, green-yellow, blue- green, purple-blue, red-violet, white and grey) for twelve consecutive weeks during the experiment. In this process, various measurements and evaluations were conducted for each different colours regarding attention, emotion, and behaviours. The results show that learners' attention notably increased in the red-purple and yellow wall colours and decreased in the orange, purple, red, and blue wall colours. The students mostly preferred green-yellow, blue- green, orange, purple, and blue wall colours, and the least preferred ones were grey, yellow, and red-purple colours. The red, orange, green, green-yellow, blue-green, blue, and purple wall colours were perceived as positive by students. From behavioural point of view, they were more active in red, orange, yellow, and blue-green, whereas they were calmer in purple, red- purple blue, and green. In the grey wall colour environment, students were observed as bored and distracted, and there was a decrease in their attention in the course.
Keywords: 8-9-years-old children; attention; emotional response; behavioural response; colour effects; learning spaces; CURVES; INTERIOR; MOOD; Architecture